Theoretical Study on the Interaction Potential and Bound States of the Ne-Beh Complex (Journal of Atomic and Molecular Sciences, 2011)
The first two-dimensional potential energy surface for the Ne-BeH van der Waals interaction is calculated by the single and double excitation coupled-cluster theory with noniterative treatment of triple excitations [CCSD(T)]. Mixed basis sets, aug-cc-pVQZ for the Be, H and Ne atom, with an additional ($3s3p2d1f1g$) set of midbond functions are used. There is a single global minimum at $R_e=6.95 a_0$ and $θ_e=72.5^°$ with well depth -34.43607 $cm^{-1}.$ Based on the potential, the rovibrational energy level structure of the Ne-BeH complex is also investigated.
Keywords: molecular spectroscopy; van der Walls; CCSD(T); bound states.